Adesão a terapia antirretroviral, mensurada por diferentes métodos, em pacientes HIV/AIDS atendidos em hospital universitário de Goiânia - Sousa, Clarissa Alencar de (2011)
Introduction: Highly active antiretroviral therapy (HAART) changed aids morbidity and mortality profile, decreasing opportunist diseases and deaths. However, adherence is determinant to ensure long-term benefits. This study aims to compare three measures of adherence to HAART and to estimate frequency and related factors of this event. Methods Cross-sectional study conducted among 249 adults, receiving HAART in a public referral center (Hospital das Clínicas/UFG), in Goiás, from 2009 through 2010. Three measures of adherence were investigated 1) Patients who scored > 75 points at the Questionnaire CEAT-VIH (Remor E et al, 2007) were considered adherent. 2) Patients who reported taking more than 95% of the prescribed antiretroviral pills in the past 7 days were considered adherent. 3) Pharmacy refill records measure. Considered adherent those withdrew antiretroviral drugs at the correct time. The prevalence of non adherence and its 95.0% confidence interval (CI) were calculated. Agreement between measures of adherence was assessed using Kappa test. To evaluate the reliability of the measures, undetectable HIV viral load was considered the gold standard. Statistical analyses were performed by using SPSS (13.0) P <.05 was considered significant Results: The majority of participants were men (77.1%), 57.0% had > 8 years of schooling and 61.4% were taking AZT, 3TC and EFV. The prevalence of no adherence, considering missing doses in previous 7 days, was 27.2% (CI95% 17.3 -31.2). According to questionnaire CEAT-VIH, 51.0% (CI95% 49.5 – 52.5) had low/insufficient adherence. According to pharmacy refill records 37.4% (CI95% 35.0 – 39.8) were no adherent. There was a low grade of agreement between the three measures used to evaluate adherence (kappa < 0.40). Adherence was significantly associated with undetectable viral load. Adherence was not associated with gender, schooling or number of pills/day. Being a heavy alcoholic user was associated to poor adherence. Conclusions: Different measures applied to the same patients yielded different levels of adherence, although all three measures were associated with adequate virological response. The estimative of non adherence can be considered high since the majority of patients were taking a low complexity and high tolerability antiretroviral drugs combination.